PERANCANGAN SISTEM INSINERATOR SAMPAH PLASTIK LAYAK BAKAR RAMAH LINGKUNGAN DI KAMPUS UNIGAL CIAMIS - Zenal Abidin Abid; Heris Syamsuri; Ade Herdiana (Universitas Widyatama, 2023)
Good and efficient waste management with incineration technology is the conversion of combustible plastic waste materials into gaseous materials (exhaust gases), as well as hard-tocombustible solids, namely bottom ash and fly ash. One of the waste treatment systems uses open burning, and transporting it to public landfills is a separate problem. Certain types of plastic waste that should be burned to process waste have not been carried out yet because there is no waste combustion system in the form of an incinerator, so further discussion is needed. This research aims to provide enlightenment and gain knowledge about how to design an incinerator system that can be used in processing waste in the Ciamis University campus environment. The research target is the Galuh University campus environment and the community, especially those related to plastic waste decomposition systems. The research method uses CAD (Computer Aided Design) and CAE (Computer Aided Engineering) systems, namely system design, manufacture, modification, analysis, or design optimization using a computer (workstation) using CAD software. The output of this method is a technical drawing that has been analyzed by CAE.